Pedagogical Analysis of Faith in Catechetical Activities: Between Theory and Practice in Mok Parish, Flores - Agustinus Manfred Habur; Avelina Fransiska Asisi Na’u; Martinus Chen (International Journal Labs, 2025)
This study aims to analyze the application of the principles of faith pedagogy in catechesis activities of the people in Mok Parish, Flores, as well as identify the gap between theory and practice that takes place in the field. The research uses a descriptive qualitative approach with interview, observation, and documentation techniques involving parish priests, station administrators, KBG chairmen, and congregations at Waekekik Station. The results of the study show that the catechesis activities of the people are still instructive and formal, where the people are physically present but less involved in a reflective and participatory way. The factors that cause the low implementation of faith pedagogy include limited faith understanding, weak spiritual motivation, economic busyness, geographical terrain, and lack of facilitator capacity in implementing participatory methods. Analysis based on the theories of shared Christian praxis, experiential learning, and andragogy confirms that effective faith learning requires contextual experience, reflection, and dialogue of faith. This study recommends the need to update the catechesis method based on faith pedagogy that is more participatory and contextual, training facilitators, and the development of catechesis materials that are relevant to the lives of rural people. This approach is expected to be able to make catechesis a means of transforming faith that is alive and grounded in the social reality of the people.